Essays on Poetry - Mills, Ralph J.; Introduction by Anania, Michael (USA Dalkey Archive Press, 2003)
"Taken from throughout Mills's career, the essays collected in this volume delve into the work of such influential writers as Wallace Stevens, Denise Levertov, Samuel Beckett, Galway Kinnell, Edith Sitwell, Theodore Roethke, Karl Shapiro, Richard Wilbur, Isabella Gardner, James Wright, David Ignatow, Donald Hall, Robert Bly, Philip Levine, and Stanley Kunitz. Mills examines how the personal element informs the works of these writers and enables them "to speak to us, without impediment, from the deep center of a personal engagement with existence." Book jacket."--Jacket.
Keywords: Poetry -- American poetry -- English poetry